2012
DOI: 10.1002/jbm.b.32698
|View full text |Cite
|
Sign up to set email alerts
|

Influence of extracellular matrix proteins in enhancing bacterial adhesion to titanium surfaces

Abstract: ECM matrix proteins promote adherence of potential periodontal pathogenic bacteria to titanium surfaces. Management of diseases such as peri-implantitis should focus on limitation of this bacterial adherence to reduce/eliminate biofilms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…On this note, the coating of titanium surfaces with laminin‐5 has been shown to promote epithelial cell adhesion . It has been previously shown that P. gingivalis interfered with oral keratinocyte cell adhesion and spreading on plastic surfaces coated with laminin‐5, and that coating of titanium disks with laminin promoted adhesion of P. gingivalis . Herein, we confirmed that P. gingivalis (the reference strain and the two included clinical isolates) clearly prevented epithelial cell adhesion on titanium–zirconia disks coated with laminin‐5.…”
Section: Discussionsupporting
confidence: 80%
“…On this note, the coating of titanium surfaces with laminin‐5 has been shown to promote epithelial cell adhesion . It has been previously shown that P. gingivalis interfered with oral keratinocyte cell adhesion and spreading on plastic surfaces coated with laminin‐5, and that coating of titanium disks with laminin promoted adhesion of P. gingivalis . Herein, we confirmed that P. gingivalis (the reference strain and the two included clinical isolates) clearly prevented epithelial cell adhesion on titanium–zirconia disks coated with laminin‐5.…”
Section: Discussionsupporting
confidence: 80%
“…This nevertheless indicates that the presence of IgG layer on the films already alleviates the remarkable impact of the special functionalization of the surface (surface grafting). In fact, the enhanced bacteria adhesion as a result of the preadsorption of IgG is not surprising, since conditioning layer (IgG layer in this case) usually promotes formation of bacterial biofilm . Many other serum protein layers, such as collagen, fibronectin and vitronectin, were reported to have similar effect.…”
Section: Resultsmentioning
confidence: 92%
“…In fact, the enhanced bacteria adhesion as a result of the preadsorption of IgG is not surprising, since conditioning layer (IgG layer in this case) usually promotes formation of bacterial biofilm . Many other serum protein layers, such as collagen, fibronectin and vitronectin, were reported to have similar effect. It was found that S. epidermidis could specifically bind Fbe sites to fibrinogen, SdrG to collagen, autolysins AtlE and Aae to vitronectin, in turn accelerating the formation of bacterial biofilm …”
Section: Resultsmentioning
confidence: 92%
“…Given that bacterial adhesion is a complex process, many research efforts have been devoted to clarifying the phenomenon from two possible perspectives: on the one hand, it is believed that the effect of adsorbed proteins on bacterial adhesion and biofilm formation is determined by surface physicochemical properties including wettability, roughness, and charge state, which could be altered by the protein adsorption process. On the other hand, some researchers believe that the specific molecular recognition between adsorbed proteins and bacterial cell wall receptors plays the decisive role, thus the conformation of the adsorbed proteins was the key point. In this work, we analyzed the relationship between the altered surface physicochemical properties and bacterial adhesion and biofilm formation of S. epidermids and E. coli .…”
Section: Resultsmentioning
confidence: 99%